Multi-Mold Design For Fishing Boats Southern Coastal Region of Java - Budianto; Priyambodo Nur Ardi Nugroho; Ruddianto (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
In general, molding or FRP ship molds can only produce 1 (one) hull shape. This is of course, contrary to the production of ships which are mostly of the customize type (based on consumer demand) and very rarely in the form of mass products to produce sister ships. The high cost in the allocation of molding certainly makes economic considerations regarding the cost of shipbuilding. With the aim of a friendly fishing boat price, of course, it can make a mainstay and ease the burden on the answer to the high demand for fishing boats in the coastal community or the South Coast of Java. Multi-mold is a ship molding solution for FRP ship material that can produce more than one hull shape. This of course, will reduce the cost of producing a ship or boat. The cost budget plan is determined in detail through a survey of material prices and conducting a price determination study with an engineering estimate approach. In the multi-mold system or components, there are the main shell structure, reinforcement frame and suppot or mold holder. The shape of the multi-mold is carefully designed which can be knocked down each constituent component. The multi-mold disassembly process is accompanied by operational instructions and 3D simulation of the multi-mold assembly. The structural strength of the multi-mold components is also analyzed so that an effective and efficient multi-mold design is obtained.